(untitled) (Experimental biology, 2016)
In the implementation of radiation consequences on the body an important role belongs to the mechanisms of repair, xenobiotics detoxification and oxidative protection. One of the effects of exposure to ionizing radiation is the formation of free radicals, which can induce oxidative stress, lead to single and multiple oxidative DNA damage, inhibit enzymes and oxidize membrane lipids, thereby supressing functional activity of cells. Maintaining a balance between the processes of formation and utilization of free radicals is an important aspect of cell life and organism as a whole. The article presents the data on analysis of polymorphisms of genes GSTP1 Ile105Val and eNOS 4a/b in Kazakhstan population, exposed to radiation for a long time as a result of living in areas surrounding former Semipalatinsk nuclear test site. During this study we obtained the frequency distribution for genotypes and alleles at polymorphic loci GSTP1 Ile105Val and eNOS 4a/b in the examined population. According to the results of statistical analysis, high level of radiation sensitivity risk revealed mutant homozygotes a/a of eNOS gene (OR = 6,15; p = 0,04).